Genus Bistorta (L.) Adans. (Polygonaceae) in Nepal - Rajbhandari, Keshab R.; Joshi, Radha; Dahal, Sajan (Journal of Plant Resources, 2008)
The genus Bistorta (L.) Adans. (Polygonaceae) in Nepal is revised and 14 species are described with synonyms, original citations and relevant references. A key to the species is worked out. Notes on distribution, phenology and ecology of the taxa are given. Bulletin of the Department of Plant Resources Vol 30, 2008 pp 47-57